KONTRIBUSI HASIL HUTAN BUKAN KAYU BAGI MASYARAKAT DI SEKITAR KAWASAN HUTAN (Studi Kasus Desa Bukaka) - Anton C. Nugroho; Terry M. Frans; Reynold P. Kainde; Hengki D. Walangitan (COCOS, 2015)
ABSTRACTParticularly, the objectives of this research are to analyze between non-timber forest product (NTFP) contribution and one of social economic aspect (education) of Bukaka household farmers community. This study is located at Bukaka village, Kotabunan District of Bolaang Mongondow Timur Regency, North Sulawesi. Technically, indepth interview was used quastionaries method to 52 respondents which are taken from April to June 2014. However, the outcome of this study shows that NTFP contributes to the household income 25,16 % (Rp. 13.552.654 annualy) including 41,67% species of flora and 58,33% of fauna speciesfrom 12 species in total which are used by household. In conclusion, contribution of NTFP is not influenced by education level.Keywords: Contributions NTFPs, Income, Socio-economic aspect, Bukaka Village.